STUDI KOMPARASI DAN PREDIKSI PENYAKIT DIABETES MELLITUS DI PROVINSI NUSA TENGGARA BARAT MENGGUNAKAN TREND - Lintang Ayu Kinanti; Melani Putri Larasati; Neha Wahyu Ardhana; Nigar Ramadhani Susanto; Nora Aurotul Jamik; Ratna Firmadani; Sherly Trinatasari; Shinta Devi Nurmala Sotya (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2024)
This study aims to compare and predict the prevalence of Diabetes Mellitus (DM) in various sub-districts and healthcenters in West Nusa Tenggara (NTB) between 2018 and 2022. The data was sourced from the Disease Management Section of the West Nusa Tenggara Provincial Health Office. The research examines the number of individuals with DM and the percentage of DM patients receiving healthcare services according to established standards. In 2018, 2019, and 2020, there was an increase in the number of patients with DM in across West Nusa Tenggara. The population of DM patients increased annually from 2018 to 2022, with the most significant increase in 2018 and 2019. However, the number of DM patients who received healthcare services according to standards was decreased in 2019. This suggests a pressing need to enhance the healthcare system in West Nusa Tenggara to improve access and the quality of care for individuals with DM. This study offers valuable insights into the challenges and advancements in healthcare services for DM patients in West Nusa Tenggara. The findings of this study serve as a foundation for improved policies and more effective health programs aimed at the issue of Diabetes Mellitus in the West Nusa Tenggara region.